Devastating Geohazards and Disaster Risk Management System in Cameroon - Christian, Guedjeo; Pierre, Wotchoko; Chenyi, Marie-Louise; Armand, Kagou Dongmo (European Journal of Applied Sciences, 2022)
Cameroon is vulnerable to natural hazards which are exacerbated by encroachment of the inhabitants into risk zones. When these geohazards occur, they tend to be disastrous in most case leaving the victims desperate. This research is aimed at investigating the devastating geohazards that occurred in Cameroon and evaluate the government response system. Using data was generated through a review of Disaster Risk Reduction literature and policy documents from the government, research institutions, academic publications and internet sources, we were able to present a concise account of the typology and of the functionality of geohazards management systems in Cameroon. The findings reveal that volcanic, landslide and floods are the most devastating geohazards in Cameroon accounting for 27%, 25% and 12% of total deaths respectively. Some of these devasting events include volcanic (Nyos 1986, 1746 deaths and Monoun 1984, 37 deaths), landslides (Limbe 2001, 24 deaths, Magba 2003, 22 deaths, Ngouache 2019, 42 deaths) and floods (Douala 2020, 4 deaths). The frequency of landslide and floods has increase in recent decades and most of the affected are not resilient to these disasters. The Disaster risk management system in Cameroon is active and not proactive and very slow in implementation. The system is highly bureaucratic and not flexible. Critical decisions are taken only at the top level and takes time to reach those to implement in the field consequently. From the finding of this paper it is primordial to empower the councils and create a comprehensive disaster management system in Cameroon, which shall involve the mitigation, preparedness, response and recovery phases.